2019
DOI: 10.1097/01.hs9.0000563976.90123.8c
|View full text |Cite
|
Sign up to set email alerts
|

Ps1425 Results of the Daratumumab Monotherapy Early Access Treatment Protocol (Eap) in Patients From Europe and Russia With Relapsed or Refractory Multiple Myeloma

Abstract: either 0, 1, 2, 3 or 4 CRAB features at initial presentation, with a score of 0 denoting a diagnosis of smouldering myeloma. We then studied the relationship between CRAB score and overall survival using Kaplan Meier curves plotted by the statistics programme SPSS. Results: Our analysis reveals that each additional CRAB feature confers a stepwise statistically significant poorer outcome in terms of overall survival as shown in Figure 1a. This result was regardless of the treatment regimen the patient received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…3 A pooled analysis of these monotherapy studies showed an overall response rate (ORR) of 31.1%, median progression-free survival (PFS) of 4.0 months, median overall survival (OS) of 20.1 months, and a manageable toxicity profile for patients treated with daratumumab at 16 mg/kg. 10 The efficacy and favorable tolerability of daratumumab monotherapy has been consistently reported from recent real-world studies performed in countries such as the United States, Korea, Poland, Spain, Italy, Russia, the United Kingdom, Hungary, and Japan, with the ORR ranging from 23% to 56.3% [11][12][13][14][15][16][17] ( Table 1).…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…3 A pooled analysis of these monotherapy studies showed an overall response rate (ORR) of 31.1%, median progression-free survival (PFS) of 4.0 months, median overall survival (OS) of 20.1 months, and a manageable toxicity profile for patients treated with daratumumab at 16 mg/kg. 10 The efficacy and favorable tolerability of daratumumab monotherapy has been consistently reported from recent real-world studies performed in countries such as the United States, Korea, Poland, Spain, Italy, Russia, the United Kingdom, Hungary, and Japan, with the ORR ranging from 23% to 56.3% [11][12][13][14][15][16][17] ( Table 1).…”
Section: Introductionmentioning
confidence: 66%
“…14 The results from a pooled analysis of 293 heavily pretreated patients with RRMM enrolled in the MMY3010 EAP of daratumumab monotherapy from Spain, Italy, Russia, and the United Kingdom revealed a similar ORR of 33.1% (VGPR in 12.3%, CR or better in 2.7%) after a median follow-up of 6.3 months. 15 In addition, the median PFS was 4.63 months, and the estimated 6month PFS rate was 42.9%. 15 The investigators emphasized that the pooled analysis had confirmed the safety profile and efficacy of DARA monotherapy in patients with heavily pretreated RRMM, without identification of new safety concerns and with maintenance of health-related quality of life during a median of 4.2 months of daratumumab treatment.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations